Medicine Dispenser Machine with Database Information System for the Senior Citizens Using Arduino Uno: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researchers created a medical dispenser machine to make obtaining medications simple and quick in a smart way. Many nurses and caregivers are overloaded and fail to do their tasks, like administering medicine to older citizens in hospitals, clinics, and nursing homes. Furthermore, a great percentage of the senior population requires medication to be healthy. The researchers used an innovative design on existing ideas, concepts, and technology. Still, they added new thoughts from other technologies that work together to develop technology and deliver new ideas to a certain product.  To test the functionalities, the developers have tested the device with the help of non-functional testing methods in the categories of performance testing, security testing, usability testing, and compatibility testing. The study results are based on the findings that eighty per cent (80%) of the respondents answered that they have poor medication management of their daily prescription. Also, the other question found in their answer is that. Many senior citizens take their prescriptions incorrectly. Based on the data gathering, the reason for incorrect medication is that many nurses and caregivers are overworked and forget to accomplish other things. Based on the test for the device’s functionality, some user testers found out how effective and helpful the device is to the other users. Based on the findings, the researchers found that Senior Citizens are more likely to forget to take their pills for maintenance and medications. Without using any device, the patients struggle more in managing their medications. With the help of this Medicine Dispenser Machine, the patients will not forget to take their pills for medications.
Keywords: Servo Driver Module; Administering medicine; Dispenser Machine; Arduino UNO; Non-functional Testing Methods